2017
DOI: 10.1261/rna.064691.117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic implications of enhanced editing by a HyperTRIBE RNA-binding protein

Abstract: We previously developed TRIBE, a method for the identification of cell-specific RNA-binding protein targets. TRIBE expresses an RBP of interest fused to the catalytic domain (cd) of the RNA-editing enzyme ADAR and performs adenosine-to-inosine editing on RNA targets of the RBP. However, target identification is limited by the low editing efficiency of the ADARcd. Here we describe HyperTRIBE, which carries a previously characterized hyperactive mutation (E488Q) of the ADARcd. HyperTRIBE identifies dramatically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(131 citation statements)
references
References 30 publications
9
120
2
Order By: Relevance
“…TRIBE was first developed in Drosophila and worked well both in S2 tissue culture cells and in fly neurons (McMahon et al 2016;Luo et al 2018;Xu et al 2018). To adapt this method to mammalian systems, we first tried the improved hyperTRIBE version with its hyperactive form of the Drosophila ADAR catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRIBE was first developed in Drosophila and worked well both in S2 tissue culture cells and in fly neurons (McMahon et al 2016;Luo et al 2018;Xu et al 2018). To adapt this method to mammalian systems, we first tried the improved hyperTRIBE version with its hyperactive form of the Drosophila ADAR catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although 4E-BP-mediated editing is enriched in the 5'UTR, editing clearly occurs elsewhere within the transcript, in fly cells as well as in mammalian cells. This could reflect 4E-BP overexpression, but it is likely that the ADARcd can also "reach" and edit a susceptible sequence element a considerable distance away from the binding site of its protein complex (McMahon et al 2016;Xu et al 2018).…”
Section: However Rna Recognition As Well As Translational Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that Sqd, Heph, and Hrb27C post-transcriptionally promote the expression of key components of the BMP signaling pathway in GSCs. In support of this model, recent studies profiling RNA targets of Hrb27C in Drosophila neuronal cell lines identified several transcripts essential for BMP signaling (McMahon et al, 2016;Xu et al, 2018). Given the complexity of the sax, tkv, and put gene loci, we postulate that hnRNPs regulate the splicing or stability of these essential BMP signaling transcripts in GSCs.…”
Section: Discussionmentioning
confidence: 67%
“…Peak fractions containing the recombinant proteins were pooled, aliquoted, and snap-frozen in liquid nitrogen. Frozen aliquots were stored at − 80 °C.TRIBETRIBE was performed as previously described(McMahon et al, 2016;Worpenberg et al, 2019;Xu et al, 2018). Briefly, for the identification of mRNA targets in S2R+ cells, Flagtagged Ythdf and Fmr1 versions fused to the catalytic domain of Adar (cdAdar) were ectopically expressed using a metal inducible expression system.…”
mentioning
confidence: 99%